Comparison of Laser Photocoagulation Using 810 nm with 20 ms and 100 ms Duration on the Progression of Neovascularization in Proliferative Diabetic Retinopathy - Muhammad Yusran; Elvioza Elvioza; Ari Djatikusumo; Rossalyn Sandra Andrisa (Majalah Oftalmologi Indonesia, 2015)
Background: The aim of this study was to compare the effectiveness of laser photocoagulation 810- nm with 20 ms and 100 ms duration to prevent the progression of proliferative diabetic retinopathy. Method: This study was prospective double blind randomized clinical trial. Twenty-eight participants who met the inclusion criteria divided into two groups to undergo laser photocoagulation by using 810 nm lasers. One group received 100 ms duration and the other received 20 ms duration. Grade 3 burns with a 200 μm spot sized were placed with both parameters. The progression of PDR was evaluated in two months follow up by using seven fields’ fundus photographs. Fluence, power and visual acuity were compared in this study. Result: Twenty five subjects completed the two months follow up. The proportion of non-progressive PDR in 100 ms group was 75.0% and in 20 ms was 76.9% (p=1.000). The power in 20 ms group increased twice than 100 ms group (1000 vs. 500 mW; p=0.000). The median fluence in 20 ms group was less than 100 ms group (6.36 vs. 15.91 J/cm2; p=0.000). Improvement of visual acuity in 20 ms and 100 ms was comparable (23.1% vs. 33,3%; p=1.000). Conclusion: The 20 ms duration showed similar result in preventing the progression of PDR compared to 100 ms duration. Keywords: Proliferative diabetic retinopathy, laser photocoagulation, diode 810 nm